Unmasking the Perky Effect: Spatial Extent of Image Interference on Visual Acuity - Reeves, Adam; Lemley, Catherine (Frontiers in Psychology, 2012)
We have previously argued that visual mental images are not substitutable for visual percepts, because the interfering effects of visual stimuli such as line maskers on visual targets differ markedly in their properties from the interfering effects of visual images (the ‘Perky effect’). Imagery interference occurs over a much wider temporal and spatial extent than masking, and unlike masking, image interference is insensitive to relative orientation. The lack of substitutability is theoretically interesting because the Perky effect can be compared meaningfully to real-line masking in that both types of interference are visual, not due to optical factors (accommodative blur or poor fixation) or to high-level factors (attentional distraction, demand characteristics, or effects of uncertainty). In this report, however, we question our earlier position that spatial extents of interference are markedly different: when images and real lines are matched in contrast, which was not done previously, their interference effects have very similar spatial extents. These data add weight to the view that spatial properties of images and percepts are similar in respect to extent. Along with the wider temporal extent and the insensitivity to orientation, the new results remain compatible with our older hypothesis that to create a clear mental image in a region of visual space, incoming signals from the eye must be suppressed (Craver-Lemley & Reeves, 1992). We have pursued this idea in this report using ‘unmasking’, in which adding elements to the visual image in the region beyond the zone of suppression reduces the Perky effect.